2020
DOI: 10.36348/sjodr.2020.v05i01.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Treatment Outcomes Using Centrographic Analysis of Skeletal Class II Malocclusion

Abstract: Aim: The main objective of the study is to assess and compare the skeletal and dental changes obtained before and after treatment using centrographic analysis in patients with class II skeletal base using three different treatment modalities-Functional, Fixed Functional and Surgical (BSSO advancement). Materials and methods: A sample of 240 retrospectively collected pre-and post-treatment lateral cephalograms of class II malocclusion treated by orthodontics or orthodontic-surgical combined approach are include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is highly likely that centrographic points are less variable than anatomical points but no variance studies have been published. More recently various applications of this method has been used by Dolce C et al, [22]; Murata S, et al, [23]; Murata S [24]; Al-Shahrani IS, et al, [25]; Nehete AB and Hazare PV [26]; Yagci A, et al, [27]; Jayapal J, et al, [28].…”
Section: Sci Forschenmentioning
confidence: 99%
“…It is highly likely that centrographic points are less variable than anatomical points but no variance studies have been published. More recently various applications of this method has been used by Dolce C et al, [22]; Murata S, et al, [23]; Murata S [24]; Al-Shahrani IS, et al, [25]; Nehete AB and Hazare PV [26]; Yagci A, et al, [27]; Jayapal J, et al, [28].…”
Section: Sci Forschenmentioning
confidence: 99%
“…10 Other systematic reviews reported reduced speech difficulties and pain especially in the early stages of treatment. 11 12 13…”
Section: Introductionmentioning
confidence: 99%